KARAKTERISTIK PENDERITA YANG BERHUBUNGAN DENGAN KEJADIAN PEMBESARAN PROSTAT JINAK - Farah Diba (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2019)
Benign prostate enlargement is a global problem in older men. The risk of benign prostate enlargement is usually experienced by those in adulthood whose risk percentages vary. As a result, it also depends on how much the risk is suffered, only a small percentage of patients show clinical symptoms, which are associated with suppression of the urethra resulting in difficulty urinating or urinary retention. These two problems/complaints can be complicated by dilation to bladder hypertrophy, hydroureter, hydronephrosis, prostatitis, kidney infection, stones and infarction. This study used 100 sample people who examined themselves at the Urology Poly of the Second Level Hospital in the Kesdam I/BB Putri Hijau, Medan. The results of this study indicate that of the four characteristics analyzed, only two factors can provide a risk of benign prostate enlargement, namely age and family track record of patients with benign prostate enlargement. Two other factors, such as obesity and marital status do not provide a risk for benign prostate enlargement.